Six thinking hats. - "De Bono, Edward" (London, 1985)
This book is a very simple concept which allows a thinker to do one thing at a time. He or she becomes able to separate emotion from logic, creativity from information, and so on. The concept is that of the six thinking hats. Putting on any one of these hats defines a certain type of thinking. It describe the nature and contribution of each type of thinking.
Keywords: Psychology